Case report: Primary hepatocellular carcinoma with portal vein tumor thrombus characterized by active tumor immune microenvironment achieving a complete response following treatment of combined immunotherapy - Zhong, Kaihang; Xu, Yuyan; Cheng, Yuan; Wen, Yaohong; Cai, Lei; He, Guolin; Huang, Huakun; Fu, Shunjun; Zhong, Xuefeng; Zheng, Yating; Chen, Tingting; Huang, Mengli; et al. (Frontiers in Immunology, 2022)
Portal vein tumor thrombus (PVTT) is a frequent complication in hepatocellular carcinoma (HCC). HCC patients with PVTT have the characteristics of less treatment tolerance and poor prognosis. Immunotherapy, especially combined immunotherapy, has been successfully used in advanced HCC. However, there are no recognized universally indicators that can predict response or resistance to immunotherapy for HCC. Herein, we reported a 58-year-old HCC patient with PVTT, cirrhosis and chronic viral hepatitis, who achieved complete response (CR) after combined immunotherapy (camrelizumab combined with sorafenib or regorafenib), according to his high enrichment of tumor-infiltrating immune cells and tertiary lymphoid structure (TLS). In this case, we revealed the characteristics of the baseline tumor immune microenvironment (TIME) in a HCC patient who responded well to combined immunotherapy, suggesting that TIME can be used to assist in clinical decision making of immunotherapy for HCC.